Different definitions of neurodegeneration produce similar amyloid/neurodegeneration biomarker group findings - Jack, Clifford R.; Wiste, Heather J.; Weigand, Stephen D.; Knopman, David S.; Mielke, Michelle M.; Vemuri, Prashanthi; Lowe, Val; Senjem, Matthew L.; Gunter, Jeffrey L.; Reyes, Denise; Machulda, Mary M.; Roberts, Rosebud; et al. (Brain (London, England : 1878), 2015)
We recently demonstrated that the frequencies of biomarker groups defined by the presence or absence of both amyloidosis (A+) and neurodegeneration (N+) changed dramatically by age in cognitively non-impaired subjects. Our present objectives were to assess the consequences of defining neurodegeneration in five different ways on the frequency of subjects classified as N+, on the demographic associations with N+, and on amyloidosis and neurodegeneration (A/N) biomarker group frequencies by age. This was a largely cross-sectional observational study of 1331 cognitively non-impaired subjects aged 50-89 drawn from a population-based study of cognitive ageing. We assessed demographic associations with N+, and A/N biomarker group frequencies by age where A+ was defined by amyloid PET and N+ was defined in five different ways: (i) abnormal adjusted hippocampal volume alone; (ii) abnormal Alzheimer's disease signature cortical thickness alone; (iii) abnormal fluorodeoxyglucose positron emission tomography alone; (iv) abnormal adjusted hippocampal volume or abnormal fluorodeoxyglucose positron emission tomography; and (v) abnormal Alzheimer's disease signature cortical thickness or abnormal fluorodeoxyglucose positron emission tomography. For each N+ definition, participants were assigned to one of four biomarker groups; A-N-, A+N-, A-N+, or A+N+. The three continuous individual neurodegeneration measures were moderately correlated (rs = 0.42 to 0.54) but when classified as normal or abnormal had only weak agreement (κ = 0.20 to 0.29). The adjusted hippocampal volume alone definition classified the fewest subjects as N+ while the Alzheimer's disease signature cortical thickness or abnormal fluorodeoxyglucose positron emission tomography definition classified the most as N+. Across all N+ definitions, N+ subjects tended to be older, more often male and APOE4 carriers, and performed less well on functional status and learning and memory than N- subjects. For all definitions of neurodegeneration, (i) the frequency of A-N- was 100% at age 50 and declined monotonically thereafter; (ii) the frequency of A+N- increased from age 50 to a maximum in the mid-70s and declined thereafter; and3 (iii) the frequency of A-N+ (suspected non-Alzheimer's pathophysiology) and of A+N+ increased monotonically beginning in the mid-50s and mid-60s, respectively. Overall, different neurodegeneration measures provide similar but not completely redundant information. Despite quantitative differences, the overall qualitative pattern of the A-N-, A+N-, A-N+, and A+N+ biomarker group frequency curves by age were similar across the five different definitions of neurodegeneration. We conclude that grouping subjects by amyloidosis and neurodegeneration status (normal/abnormal) is robust to different imaging definitions of neurodegeneration and thus is a useful way for investigators throughout the field to communicate in a common classification framework.